DELILA: A Scalable Data Acquisition System for Multi-Detector Nuclear Physics Experiments at ELI-NP - Aogaki, S.; Balabanski, D. L.; Ban, S. R.; Corbu, R.; Cuciuc, M.; Kusoglu, A.; Soderstrom, P.-A. (IEEE transactions on nuclear science, 2025)
Modern nuclear physics experiments require flexible data acquisition (DAQ) systems for high data rates from diverse detector arrays. This paper presents DELILA (Digital ELI-NP List-mode Acquisition), an open-source DAQ system for high-throughput experiments at the Extreme Light Infrastructure - Nuclear Physics (ELI-NP) facility. DELILA employs a distributed, modular architecture with five components: Data Sources, Merger, Data Sinks, User Interface (UI), and Application Programming Interface (API). The system supports triggerless list-mode acquisition from silicon strips, scintillators, and germanium detectors using CAEN digitizers with various firmware (FW) (Digital Pulse Processing - Pulse Shape Discrimination (DPP-PSD), Pulse Height Discrimination (DPP-PHA), Charge Integration (DPP-QDC), waveform recording). Key features include robust clock synchronization, network transparency for distributed control, and optimized low-latency data transfer. Performance evaluation demonstrates sustained acquisition at 100 kHz per channel with FELib libraries and 2 MHz for single-channel 2730 digitizers. The system achieves 60 MB/s data rates with compact 30-byte events, enabling efficient storage. DELILA scales from 3 to 320 channels with real-time monitoring and event rate displays updated every 1-10 seconds. The Angular-based web interface with RESTful API facilitates remote operation and automated monitoring integration. Comprehensive testing using PuppEx signal generation validated stable operation across multiple digitizer configurations, with performance limited by disk I/O rather than acquisition electronics. DELILA's open-source design promotes collaborative development and customization for diverse nuclear physics experimental requirements [1].